2016
DOI: 10.1097/inf.0000000000001074
|View full text |Cite
|
Sign up to set email alerts
|

Antiretroviral Therapy in Severely Malnourished, HIV-infected Children in Asia

Abstract: Background Information on antiretroviral therapy (ART) use in HIV-infected children with severe malnutrition (SM) is lacking. We investigated long-term ART outcomes in this population. Methods Children enrolled in the TREAT Asia Pediatric HIV Observational Database who had SM (weight-for-height or BMI-for-age z-score <−3) at ART initiation were analyzed. Generalized estimating equations were used to investigate poor weight recovery (weight-for-age z-score <−3) and poor CD4% recovery (CD4% <25), and competing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
12
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 23 publications
(23 reference statements)
3
12
1
1
Order By: Relevance
“…The impact of this strategy may be higher in low‐income regions due to rarer availability of laboratory techniques that allow close monitoring of the response to ART. An advanced immunological stage or the presence of a high viral load has been associated with a poorer nutritional status . This agrees with the findings of this study, where the presence of acute underweight increased fourfold the risk of moderate‐severe immunodeficiency.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The impact of this strategy may be higher in low‐income regions due to rarer availability of laboratory techniques that allow close monitoring of the response to ART. An advanced immunological stage or the presence of a high viral load has been associated with a poorer nutritional status . This agrees with the findings of this study, where the presence of acute underweight increased fourfold the risk of moderate‐severe immunodeficiency.…”
Section: Discussionsupporting
confidence: 92%
“…Although ART is effective in improving the nutritional status, a significant percentage of patients continue to be nutritionally deficient , so it seems appropriate to support the initiation of ART with a nutritional intervention. Malnourished patients show worse immune reconstitution after the initiation of ART than patients with a normal nutritional level .…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have confirmed these general findings in Asia and many African countries (Table 2). Studies in Asia (primarily Thailand and China) have reported mean z-scores of −2.4 to −1.7 for HAZ and −2.6 to −1.1 for WAZ, with corresponding high prevalences of stunting and underweight [1618].…”
Section: Adolescent Growth Measures Prior To Art Initiationmentioning
confidence: 99%
“…In LRS, the increases in weight and height after ART initiation are somewhat more striking than those in HRS, with increases in mean z-scores after 2 years ranging from 0.4–1.0 in HAZ, and 0.4–1.5 in WAZ (see Table 2) [12,1618,20]. McGrath reported a mean increase of 0.40 in HAZ and 1.03 in WAZ after 24 months on ART [11].…”
Section: Growth In Hiv-infected Adolescents After Art Initiationmentioning
confidence: 99%
“…HIV infection in children has been associated with growth delays in terms of weight (wasting and underweight) and height (stunting) [19]. Antiretroviral treatments (ART) have been shown to have a positive impact on the evolution of the anthropometric parameters [813], but studies have mostly focused on the improvement of the weight-for-age z-score (WAZ) [9, 1418]. Results of the several studies analyzing the effect of ART on height-for-age z-score (HAZ), a better indicator of the general development of children in the long term [19–23] are conflicting, some suggesting a favourable effect [2427] and others not [2832].…”
Section: Introductionmentioning
confidence: 99%